Квинтилиан и Дионисий Галикарнасский о греческих эпиках [Elizaveta Varganova: Quint. Inst. X, 1, 52–54 and Dion. Hal. De imit. II, 2–4] - Варганова, Е. С. (Hyperboreus, 2007)
As early as the 16th century, scholars were already noticing that in his analysis of Greek literature, Quintilian is much indebted to Dionysius of Halicarnassus – the extant epitomized version of De imitatione II and Inst. X, 1, 46–84 show close resemblance. Nowadays there is still no opinio communis about the relation between Quintilian and Dionysius, although some commentators tacitly approve the theory of common source set forth by L. Radermacher. In this article, the Greek and Latin characteristics of epic poets (Hesiodus, Antimachus and Panyasis) are compared, as their similarity is the most apparent.Quintilian’s characterization is obviously more profound and versatile. He discusses the merits and demerits of each poet, while the Greek text of epitome contains laudable characteristics only. Quintilian’s criticism not only demonstrates his own personal likes and dislikes (e.g. for the austere manner of Antimachus), but also shows his practical experience as a teacher and a reader (cf. his reproach on Hesiodus with lack of sublimity and abundance of names). And as long as we admit Quintilian’s censorious remarks to be self-dependent, while his positive comments are very similar to the Greek text, we can assert that it was already the epitomized text (most likely in the form of a textbook, without an author’s name) which he read and used as a source for his treatise. The absence of direct references to Dionysius confirms this assumption. The differences between Inst. and De imit. evolve when the Roman critic interprets the text of the epitome or gives his own opinion. Thus, there is no need to allege a common source for Quint. Inst. X, 1, 52–54 and Dion. Hal. De imit. II, 2–4.